Identification of an IncHI5-like plasmid co-harboring blaNDM−1 and blaOXA−1 in mcr-8.1-positive Klebsiella pneumoniae isolate - Liu, Xu; Zhang, Tingting; Yu, Zhiyang; Qin, Shangshang; Zhang, Muchen; Li, Yan (Frontiers in Microbiology, 2025)
The emergence of polymyxin-resistant carbapenem-resistant Klebsiella pneumoniae (CRKP) severely limits clinical treatment options and poses a significant threat to anti-infective therapy. In this study, we investigated the genetic characteristics of an IncHI5-like plasmid co-harboring blaNDM−1 and blaOXA−1 in an mcr-8.1-positive clinical CRKP isolate using a combination of MIC testing, conjugation experiments, bacterial whole-genome sequencing, and bioinformatics analyses. The ST626 CRKP strain KP19-2581, isolated from a human clinical infection, exhibited a multidrug-resistant (MDR) phenotype. Whole-genome sequencing revealed that the colistin resistance gene mcr-8.1 was located on an IncFIA/IncFII plasmid, flanked by the conserved structure IS903B-orf-mcr-8.1-orf-IS903B. In addition, strain KP19-2581 carried a novel IncHI5-like MDR plasmid, designated pKP19-2581-367k-HI5-NDM1, which co-harbored the blaNDM−1 and blaOXA−1 genes. This plasmid contained two MDR regions, harboring a diverse array of resistance genes across multiple antibiotic classes. The dissemination of blaOXA−1 in variable region is related to the structure of class 1 integron, while IS26 mediates the integration of blaNDM−1 on IncHI5-like plasmid. Notably, this is the first report of an IncHI5-like plasmid carrying both blaNDM−1 and two copies of blaOXA−1, along with multiple resistance genes and insertion sequences. Given its potential to acquire additional resistance determinants, this plasmid may serve as a reservoir for further antimicrobial resistance evolution, underscoring the urgent need for surveillance of IncHI5 plasmids to mitigate their clinical and epidemiological impact.